Endoscopic Treatment of Previous Cesarean Scar Defect in Women with Postmenstrual Bleeding: A Retrospective Cohort Study - Ning-Ning Zhang; Guang-Wei Wang; Qing Yang (Journal of Investigative Surgery, 2021)
Objective To compare the incidence of postmenstrual bleeding after hysteroscopic resection versus laparoscopic repair of previous cesarean scar defect (PCSD). Materials and methods Retrospective analysis of computerized patient records. For the diagnosis of PCSD, patients underwent transvaginal ultrasound first without and then with saline-assisted sonohysterography. Hysteroscopic PCSD resection was performed under sonographic guidance, while laparoscopic repair was guided by hysteroscopy for the confirmation of scar margins. Results Records of 62 patients presenting with PCSD-related postmenstrual bleeding were included in analysis. Hysteroscopic surgery had significantly shorter operative time compared to the laparoscopic approach (Mean =30.9 vs 71.0 minutes; p < 0.001). Blood loss and hospital stay were significantly less (p < 0.001) in hysteroscopic resection (10.4 ± 4.6 ml and 2.1 ± 0.4 days) than in laparoscopic repair (36.6 ± 4 ml, and 4.6 ± 1 days). After surgical interventions, the postmenstrual bleeding was resolved or improved. The effectiveness rates of hysteroscopic resection and laparoscopic repair were 91.4% and 96.3%, respectively. Incidence of post-treatment postmenstrual bleeding was not significantly different between hysteroscopy and laparoscopy (OR= 1.29 [95% confidence interval 0.367, 4.86]; p = 0.662). Pretreatment postmenstrual bleeding was associated with time since cesarean section (B= −0.091 [−0.158, −0.023]; p = 0.01) and PCSD length (B = 0.502 [0.085, 0.919]; p = 0.019). Conclusion Both hysteroscopic resection and laparoscopic repair of PCSD yield comparable efficacy in reducing postmenstrual bleeding. However, hysteoroscopic resection of PCSD is associated with comparatively shorter operative time, less blood loss, and shorter hospital stay.